Study on the Mitochondrial Genome of Variants Carrying mt.3243A>G from Type-2 Diabetes Mellitus and Cataract Patients in Indonesia - Iman Permana Maksum; Rahmaniar Mulyani; Khomairi Hasan; Mamlikatu Ilmi Azizah; Wanda Destiarani; Ahmad Fariz Maulana; Muhammad Yusuf; Toto Subroto (HAYATI Journal of Biosciences, 2023)
The association of type-2 diabetes mellitus (T2DM) and cataract with mtDNA mutation has been reported before. Despite the high prevalence of DM and cataract in Indonesia, a study of the mtDNA variants in Indonesia in correlation with the two diseases is still limited. MT.3243A>G is one of the hotspots mutations for mitochondrial diseases, but the explanation for its occurrence in patients with pure cataract is still elusive. Therefore, the objective of this study was to analyze the mitochondrial genome variants from T2DM and cataract patients in Indonesia using the direct sequencing method. The homology analysis of the genome to the Cambridge reference sequence resulted in 86 variants, including 20 variants that cause amino acid substitutions. Based on the Mitomap data, 17 of the 20 variants were novel. Upon comparison with the 12 normal variant genomes, 11 of 17 variants were suggested to be associated with T2DM and cataract diseases since they code the protein in complex-I (ND4L, ND5, and ND6), complex-III (cytb), and complex-V (ATP6) of the respiratory complex. Interestingly, MT.3316G>A, for the first time, is shown in a pure cataract patient. In addition, the novel phenotype of MT.5460G>A and MT.10398A>G were revealed, which are T2DM and cataract in one patient. Based on our study, these diseases might be related to the disruption of the ATP metabolism due to the structure and function changes of proteins involved in the respiratory complex. This discovery is expected to offer an understanding of the origins of gene-level clinical differences, particularly in Indonesia.